Faktor-Faktor yang Mempengaruhi Nilai Perusahaan pada Perusahaan Manufaktur Industri Sektor Barang Konsumsi di Bursa Efek Indonesia Periode 2015-2019 - Sholikha Nur Rohmah; Endang Masitoh; Yuli Chomsatu (Universitas Batanghari Jambi, 2021)
This study aims to determine company size, company age, capita1 structure, financia1 performance and dividend po1icy on firm value. The research method used is a quantitative method. The data used in this study is secondary data in the form of financia1 reports from the website (www.idx.co.id). The popu1ation in this study are industria1 manufacturing companies in the consumer goods sector 1isted on the Indonesia Stock Exchange (IDX) from 2015 to 2019. The samp1e was se1ected from the purposive samp1ing method and obtained a samp1e of 19 companies from severa1 predetermined criteria. The ana1ytica1 technique used in this study is mu1tiple 1inear regression ana1ysis with the he1p of SPSS version 22 program. The resu1ts of the ana1ysis show that firm size, firm age and dividend po1icy affect firm value. Whi1e, capita1 structure and financia1 performance have no effect on firm value. The resu1ts of this study are expected to add insight into know1edge and become usefu1 inputs about the value of the company in a company and re1ated agencies.